TANTANGAN PUSTAKAWAN PERGURUAN TINGGI DALAM MEMBERIKAN LAYANAN PRIMA DENGAN BERBASIS TEKNOLOGI INFORMASI - Rifngati, Endang (IAIN Tulungagung, 2016)
Advances in technology have an impact in all areas, as well in the college library as one of the institutions information management, application of information technology in libraries is used to improve the services that are owned by the library. Librarians as one important component in the library served to take advantage of existing technology is a new challenge for librarians who previously applying conventional based services should be transformed into information technology-based services. Improving the competence of librarians must continue to be done in order to create a professional librarian. By having professional competence is expected librarian is always ready to face any changes that occur.Kata Kunci: Pustakawan Perguruan Tinggi, Layanan Prima, Teknologi Informasi